Thai Society Development with a Thorough Knowledge and Understanding of the Three Planes - Muddavo /Pettra, PhraPaladAmpol; Phrakhrupawanpattanabundit (Journal of Graduate Saket Review, 2025)
The book “Thai Society Development with a Thorough Knowledge and Understanding of the Three Planes” has a total of 5 content topics as follows: 1) summary structure of the contents of the Three Planes (Tebhumi), which is about the Tebhumi (3 levels) and the Catutthabhumi (4 levels); 2) general observations helping to understand the Tebhumi, which is about the three cycle of rebirth (Tevaṭṭa), comparing the background and literary works; 3) morality in Tebhumi Phra Ruang, which is about the Ten Royal Virtues, the Ten Meritorious Deeds, and the Morality of Rulers; 4) the scope of Influence of Tebhumi, which is about morality, influence on thought and belief in heaven and hell of rulers, principles of governance and influence on thought in the Sukhothai and Ayutthaya Era; 5) correct thoughts and attitudes toward the Tebhumi, which is about the Principle of Karma, the Principle of Tilakkhana, and the Principle of Tebhumi for the creation of Thai society. In summary, Tebhumi Phra Ruang is about the realms of existence or the process birth and death (Samsara). There are factors that cause one to be born into various realms, namely defilement (Kilesa), deed (Karma), and result (Vipāka), which are the components of the process birth and death (Samsara). The interesting content that leaders use in governing is the Ten Royal Virtues. Dhamma that promotes governance, such as the Five Precepts and the way of making merit (Puññakiriyāvatthu). Whereas, dhamma at a higher level that teaches practitioners to understand life, such as Paticcasamuppāda and the Three Characteristics, etc.